Pricing capabilities: the design, development, and validation of a scale. Issue 1 (11th March 2014) - Liozu, Stephan; Hinterhuber, Andreas
Abstract : Purpose: – The literature has paid increased attention to pricing capabilities as a set of distinctive, complex activities, routines, and processes that drive company performance. Despite this emphasis, little research has addressed the pricing-capabilities construct itself, and no accepted measure of pricing capabilities exists. The purpose of this paper, therefore, is to document the design, development, and validation of a dedicated pricing-capabilities scale, PRICECAP. Design/methodology/approach: – Qualitative plus three quantitative surveys. Findings: – The present research describes the development of a ten-item measure, PRICECAP, that can be used to assess organizational capabilities related to pricing. Research limitations/implications: – The reliability and validity of the scales were assessed through three separate quantitative studies using exploratory and confirmatory analysis. The PRICECAP scale has a variety of potential applications and can serve as a framework for future empirical research in marketing theory as well as an instrument to assess, compare, and develop pricing capabilities in marketing practice. Originality/value: – Empirical research has provided scales to measure value creation but a scale to measure value capture – i.e. pricing – capabilites is lacking. This study covers this gap and provides a new, parsimonious, ten-item construct to measure pricing capabilities.